La Universidad de Costa Rica: 1972-1990. Transformaciones, crisis y perspectivas - Araya Pochet, Carlos (1990)
Discusses the internal condition of the University of Costa Rica in the 1970s. The III University Congress gave way to significant changes. It also studies the relationship between the University, the State, and society at large.